Prefrontal Brain Asymmetry: A Biological Substrate of the Behavioral Approach and Inhibition Systems - Sutton, Steven K.; Davidson, Richard J. (Psychological Science, 1997)
Resting anterior brain electrical activity, self-report measures of Behavioral Approach and Inhibition System (BAS and BIS) strength, and general levels of positive and negative affect (PA and NA) were collected from 46 unselected undergraduates on two separate occasions Electroencephalogram (EEG) measures of prefrontal asymmetry and the self-report measures showed excellent internal consistency reliability and adequate test-retest stability Aggregate measures across the two assessments were computed for all indices Subjects with greater relative left prefrontal activation reported higher levels of BAS strength, whereas those with greater relative right prefrontal activation reported higher levels of BIS strength Prefrontal EEG asymmetry accounted for more than 25% of the variance in the self-report measure of relative BAS-BIS strength Prefrontal EEG, however, was not significantly correlated with PA or NA, or the relative strength of PA versus NA Posterior asymmetry was unrelated to the self-report measures